2019
DOI: 10.1055/s-0039-1683936
|View full text |Cite
|
Sign up to set email alerts
|

Pentalogy of Cantrell in Full Term Neonate

Abstract: Pentalogy of Cantrell (PC) is an uncommon congenital disorder characterized by severe defects in the chest and abdomen, including abdominal visceral prolapsed via umbilical cord (omphalocele), defect in the lower part of the sternum, defect in the front of the diaphragm, defects in the anterior part of the pericardium, and the ectopiacordis. Here, we report a 2-hour-old girl, weighing 3,500 g, who was referred to Shahid Madani Hospital in Khorramabad due to the large omphalocele on her chest with pulsating mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…PC is a rare congenital malformation, which was first reported by Cantrell in 1958 and revised by Toyama in 1972 ( 2 ). PC can be diagnosed by ultrasound in early pregnancy ( 3 ). Prenatal diagnosis helps families to make an informed decision on whether to continue pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PC is a rare congenital malformation, which was first reported by Cantrell in 1958 and revised by Toyama in 1972 ( 2 ). PC can be diagnosed by ultrasound in early pregnancy ( 3 ). Prenatal diagnosis helps families to make an informed decision on whether to continue pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the disease varies accordingly. In some cases, the heart protrudes beyond the chest and abdomen, as if the heart is beating outside the body, especially in patients with omphalocele and abdominal fissure ( 3 ). There are many kinds of deformities in this reported case, which are consistent with the manifestation of complete PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of hypothyroidism is reported with great variability due to geographical and ethnical variations, screening protocol of thyroid hormone and genetic diversity. Its prevalence in Iran is reported higher than other regions [ 7 ]. A cross-sectional study conducted in the central part of Iran on more than 400,000 neonates reported that the prevalence transient congenital hypothyroidism is this region is 1 in 294 live births [ 8 ].…”
Section: Introductionmentioning
confidence: 99%